2011
DOI: 10.3955/046.085.0221
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Prairie-Oak Butterflies in Oregon, Washington, and British Columbia

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…It is currently unknown how early season (July) or very late season (late October, after fall rains have begun) burns might influence invasive species cover and native species composition and structure. These types of burns may encourage heterogeneous fire severity and, therefore, help to achieve some ecological objectives related to community structure by leaving unburned resource patches from which fire-sensitive species may more readily recolonize burned areas (Schultz and Crone 1998, Panzer 2002, Schultz et al 2011.…”
Section: Fire Seasonmentioning
confidence: 99%
See 1 more Smart Citation
“…It is currently unknown how early season (July) or very late season (late October, after fall rains have begun) burns might influence invasive species cover and native species composition and structure. These types of burns may encourage heterogeneous fire severity and, therefore, help to achieve some ecological objectives related to community structure by leaving unburned resource patches from which fire-sensitive species may more readily recolonize burned areas (Schultz and Crone 1998, Panzer 2002, Schultz et al 2011.…”
Section: Fire Seasonmentioning
confidence: 99%
“…However, Dunwiddie (2002) found that multiple burns on a prairie resulted in responses by individual species that differed widely in magnitude, direction and duration between burns. Streaked horned lark (Eremophila alpestris strigata), a Federal candidate species, benefits from open and very sparsely vegetated habitat, so frequent fire may improve conditions for these birds (Pearson et al 2005), but this prescription may not be appropriate for certain butterfly species (Schultz et al 2011). Providing detailed knowledge about fire regime impacts on high fidelity prairie and oak woodland species will inform fire management plans and help to improve the utility of fire as a restoration tool.…”
Section: Future Directionsmentioning
confidence: 99%
“…Native annuals are a notable example of a group of species that is now uncommon in many prairies, likely due to the lack of frequent disturbances that historically would have provided areas for them to establish in (Dunwiddie et al 2006). It probably is no coincidence, therefore, that this loss has had cascading effects: some of these species (e.g., Collinsia parviflora, Collinsia grandiflora, Plectritis congesta, and Triphysaria pusilla) are host plants for rare butterfly species (Schultz et al 2011). Thus, in addition to the losses of plant species, most prairie/oak ecosystems have almost certainly also suffered significant losses of mammals (Stinson 2005), birds (Altman 2011), butterflies (Schultz et al 2011), and other invertebrates (Fazzino et al 2011).…”
Section: Historical Contextmentioning
confidence: 99%
“…It probably is no coincidence, therefore, that this loss has had cascading effects: some of these species (e.g., Collinsia parviflora, Collinsia grandiflora, Plectritis congesta, and Triphysaria pusilla) are host plants for rare butterfly species (Schultz et al 2011). Thus, in addition to the losses of plant species, most prairie/oak ecosystems have almost certainly also suffered significant losses of mammals (Stinson 2005), birds (Altman 2011), butterflies (Schultz et al 2011), and other invertebrates (Fazzino et al 2011). The remaining populations occupy smaller, degraded habitats and are increasingly vulnerable to extirpation.…”
Section: Historical Contextmentioning
confidence: 99%
See 1 more Smart Citation